Effect of high-fat mixed lipid diet and swimming on fibre types in skeletal muscles of rats with colon tumours - Vika Smerdu; Martina Perše (European Journal of Histochemistry, 2018)
Skeletal muscle fibre types, whose characteristics are determined by myosin heavy chain (MyHC) isoforms, can adapt to changed physiological demands with changed MyHC isoform expression resulting in the fibre type transitions. The endurance training is known to induce fast-to-slow transitions and has beneficial effect in carcinogenesis, whereas the effect of an excessive fat intake and its interaction with the effect of swimming are less conclusive. Therefore, we studied the effect of high-fat mixed lipid (HFML) diet and long-term (21-week) swimming on fibre type transitions and their average diameters by immunohistochemical demonstration of MyHC isoforms in slow soleus (SOL), fast extensor digitorum longus (EDL), and mixed gastrocnemius medialis and lateralis (GM, GL) muscles, divided to deep and superficial portions (GMd, GMs, GLd, GLs), of sedentary and swimming Wistar rats with experimentally (dimethylhydrazine) induced colon tumours and fed either with HFML or low-fat corn oil (LFCO) diet. HFML diet induced only a trend for fast-to-slow transitions in SOL and in the opposite direction in GMd. Swimming triggered significant transitions in unexpected slow-to-fast direction in SOL, whereas in GMs the transitions had tendency to proceed in the expected fast-to-slow direction. The average diameters of fibre types were mostly unaffected. Hence, it can be concluded that if present, the effects of HFML diet and swimming on fibre type transitions were counteractive and muscle-specific implying that each muscle possesses its own adaptive range of response to changed physiological conditions.